(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
Bubble electrospinning is a novel method to produce ultrafine nanofibers. In this work, a mathematical model of the electric field distribution in a critical state was established for bubble electrospinning process and was numerically simulated using finite element method. The results indicated that the maximum electric force occurred at the tip of the bubble, it is probably for this reason that the first jet occurs at the tip of the bubble, when the electrical force exceeds the surface tension, which also possibly induces bubble bursting.